Nitric Oxide (NO) in Plant Heat Stress Tolerance: Current Knowledge and Perspectives - Parankusam, Santisree; Adimulam, Srivani S.; Bhatnagar-Mathur, Pooja; Sharma, Kiran K. (Frontiers in Plant Science, 2017)
High temperature is one of the biggest abiotic stress challenges for agriculture. While, Nitric oxide (NO) is gaining increasing attention from plant science community due to its involvement in resistance to various plant stress conditions, its implications on heat stress tolerance is still unclear. Several lines of evidence indicate NO as a key signaling molecule in mediating various plant responses such as photosynthesis, oxidative defense, osmolyte accumulation, gene expression and protein modifications under heat stress. Furthermore, the interactions of NO with other signaling molecules and phytohormones to attain heat tolerance have also been building up in recent years. Nevertheless, deep insights into the functional intermediaries or signal transduction components associated with NO-mediated heat stress signaling are imperative to uncover their involvement in plant hormone induced feed-back regulations, ROS/NO balance and stress induced gene transcription. Although progress is underway, much work remains to define the functional relevance of this molecule in plant heat tolerance. This review provides an overview on current status and discuss knowledge gaps in exploiting NO, thereby enhancing our understanding of the role of NO in plant heat tolerance.